Estimates of global research productivity in primary ovarian insufficiency from 2000 to 2021: Bibliometric analysis - Zhang, Xudong; Lu, Yimeng; Wu, Shanshan; Zhao, Xinyang; Li, Shuyu; Zhang, Siwen; Tan, Jichun (Frontiers in Endocrinology, 2022)
Background Primary ovarian insufficiency (POI) is a heterogeneous disease with diverse clinical phenotypes and etiologies, which is defined as ovarian dysfunction under the age of 40 years. The global prevalence of POI is approximately about 1.1%, and it severely affects female fertility. Nevertheless, bibliometric analysis in this field is extremely limited. We aimed to visualize the research hotspots and trends of POI using bibliometric analysis and tried to predict the future development of this field. Methods The original articles regarding POI were culled from the Web of Science Core Collection. Countries, institutions, journals, authors, and keywords in this field were visually analyzed by employing CiteSpace software and Microsoft Excel 2021 software. Results A total of 2,999 publications were included for further bibliometric analysis after screening the titles and abstracts stringently. The number of literature regarding POI significantly increased yearly. These publications come from 78 countries. The USA was dominant in the field of POI in terms of the number of publications (865), average citations per item (57.36), and h-index (112). The Institut National De La Sante Et De La Recherche Medicale Inserm is the most high-yield institution in this field with 351 publications. Fertility and Sterility ranked first with the highest number of publications (152), followed by Human Reproduction (138). According to the keyword cluster analysis from 2000 to 2021, the eight keyword clusters encountered frequently were apoptosis, osteoporosis, fertility preservation, mutation, fragile x syndrome, adrenal insufficiency, DNA repair, ovarian reserve. Keyword citation burst analysis revealed that whole-exome sequencing, ovarian tissue cryopreservation, and DNA repair had a citation burst until 2021. Conclusions Great progress has been made in POI research over the past 20 years, which is widely researched but unevenly developed in the world. In terms of influence, the United States may be in the lead. The research hotspots in POI are mainly pathogenesis and treatment, including genetic mutation, hormone therapy, fertility preservation, and stem cell transplantation.